ANALISIS PENGGUNAAN ALAT BERAT TERHADAP WAKTU DAN BIAYA (STUDI KASUS : PROYEK JALAN RAYA BABATBOJONEGORO KM 72-73) - Intan Mayasari; Santi Ayu Sari (Faculty of Engineering, Universitas Islam Darul Ulum Lamongan, 2023)
Roads are infrastructure built by the government to facilitate regional development so that they become assets that must be managed and function optimally. The transportation infrastructure and facilities system as a basic infrastructure is a prerequisite for the economic movement of the region, where the supporting system and transportation infrastructure drivers play a major role in the efficiency and effectiveness of regional economic activities. The purpose of this study is to determine the time and cost of using heavy equipment used in Babat-Bojonegoro Highway Project KM 72-73 completion on paving work. This research uses the work capacity analysis method, namely by calculating data to find the working capacity of the heavy equipment used, as a basis for calculating the time and cost required for heavy equipment in the implementation of paving work. From the analysis of the time required by heavy equipment in paving work with a volume of 3612 tons / m3 is 167,5 hours or 24 days. For the total cost of heavy equipment analyzed in paving work amounting to Rp. 405.486.106.